2008
DOI: 10.1111/j.1540-6237.2008.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Policy Attitudes: Issues, Geographical Scale, and Political Trust*

Abstract: Objectives. This article examines environmental policy attitudes, focusing on the differences in preferences across issue type (i.e., pollution, resource preservation) and geographical scale (i.e., local, national, global). In addition, we study whether an individual's trust in government influences environmental policy attitudes. Methods. Analyzing data from the 2007 Cooperative Congressional Election Study, we estimate a series of OLS regression models to examine the public's environmental policy attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
135
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(150 citation statements)
references
References 21 publications
11
135
3
1
Order By: Relevance
“…In testing these last two hypotheses, this study builds on prior research arguing that trust, including particularly political trust, shapes support for environmental protection (e.g., Duit 2010; Hammar and Jagers 2006;Harring 2013;Konisky, Milyo, and Richardson 2008;Lubell 2002;Meyer and Liebe 2010;Rudolph and Evans 2005). 9 Previous studies have all, however, all been based on observational data.…”
Section: Public Support For Environmental Taxesmentioning
confidence: 99%
“…In testing these last two hypotheses, this study builds on prior research arguing that trust, including particularly political trust, shapes support for environmental protection (e.g., Duit 2010; Hammar and Jagers 2006;Harring 2013;Konisky, Milyo, and Richardson 2008;Lubell 2002;Meyer and Liebe 2010;Rudolph and Evans 2005). 9 Previous studies have all, however, all been based on observational data.…”
Section: Public Support For Environmental Taxesmentioning
confidence: 99%
“…Visual inspection of the scatter plot in Figure 2 suggests the importance of one of those potentially confounding factors: the level of political support for a plan. Numerous scholars have explored the role partisanship plays in support for climate change policies, finding that Democratic constituencies are generally more supportive of public action on climate change (Dunlap and McCright 2008;Konisky et al 2008;Zia and Todd 2010). Scholars have also studied states' adoption of renewable portfolio standards as a way to encourage the development of low-carbon energy generation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous studies have identified links between demographic factors and levels of support for environmental policy (Dietz et al, 1998;Elliot et al, 1997;Klineburg et al, 1998;Konisky et al, 2008;O'Connor et al, 2002;Torras and Boyce 1998;Zahran et al, 2006;Zahran et al, 2008a;Zahran et al 2008b). Willingness to absorb the cost of implementing climate change initiatives increases with successive levels of education (Dietz et al, 1998;Elliott et al, 1997;Klineburg et al, 1998;Lubell et al, 2006;O'Connor et al, 2002;Zahran et al, 2008a;Zahran et al 2008b).…”
Section: Collective Interest and Drivers Of Climate Change Actionmentioning
confidence: 99%
“…Liberalism has been linked to support for environmental policy in the US (see for example Konisky et al, 2008;Zahran et al 2008a) where the dual party system makes distinguishing between liberal (Democrat) voters and people with a more conservative (Republican) political ideology relatively straight forward. The existence of multiple parties in the UK, and the fact that over 20% of English local councils are controlled by more than one party, clouds this distinction somewhat.…”
Section: Social Capacitymentioning
confidence: 99%
See 1 more Smart Citation